Diversity, Physicochemical and Technological Characterization of Elite Cassava (Manihot esculenta Crantz) Cultivars of Bantè, a District of Central Benin - Abadjayé Faouziath Sanoussi; Laura Yéyinou Loko; Hyacinthe Ahissou; Adidjath Koubourath Adjahi; Azize Orobiyi; Angelot Paterne Agré; Paulin Azokpota; Alexandre Dansi; Ambaliou Sanni (The Scientific World Journal)
Cassava is one of the staple food crops contributing significantly to food and nutrition security in Benin. This study aimed to assess the diversity of the elite cassava cultivars of Bantè district, determine the physicochemical properties of the most preferred ones as well as the sensory attributes of their major derived products (gari and tapioca), and compare them with the farmers’ and processors’ perception on their technological qualities. The ethnobotanical investigation revealed existence of 40 cultivars including 9 elites that were further classified into three groups based on agronomics and technological and culinary properties. Clustered together, cultivars Idilèrou, Monlèkangan, and Odohoungbo characterized by low fiber content, high yield of gari and tapioca, and good in-ground postmaturity storage were the most preferred ones. Their physicochemical analysis revealed good rate of dry matters (39.8% to 41.13%), starch (24.47% to 25.5%) and total sugars (39.46% to 41.13%), low fiber (0.80% to 1.02%), and cyanide (50 mg/kg) contents. The sensory analysis of their gari and tapioca revealed very well appreciated (taste, color, and texture) products by the consumers. The confirmation by scientific analysis of the farmers’ perception on qualities of the most preferred cultivars indicated that they have good knowledge of their materials.